Onion Peel Powder’s Impact on the Leptin Receptors in the Hippocampus of Obese Rats - Małgorzata Komar; Monika Michalak-Majewska; Radosław Szalak; Agata Wawrzyniak; Waldemar Gustaw; Wojciech Radzki; Marcin B. Arciszewski (Applied Sciences)
The bioactive components present in onion peel powder are a promising factor in preventing/treating obesity. Overweight/obesity causes metabolic changes, which can lead to leptin resistance in the central nervous system (CNS) and, thus, to structural and functional changes in the brain. Objectives: The presented study focused on evaluating the influence of a diet supplemented with onion peel powder on the immunoexpression of leptin receptors (LepRs) in the hippocampus in obese rats and the potential anti-obesity role of the onion in the brain. Methods: To induce obesity, the animals were given a high-energy chow containing lard and sucrose. Onion skin powder was used to modify the standard and high-energy diets (10.5 g per rat/week) of Wistar rats in a 14-week experiment followed by a brain IHC study. Results: The effect of the onion diet on the expression of neuronal LepRs and astrocytes in the hippocampus was analyzed. Obese animals receiving onion in the diet showed significant growth in the average number of immunoreactive LepR (LepR-IR) neurons (p = 0.00108) and their average size (p = 0.00168) in the CA1 field of the hippocampus. Meanwhile, in obese rats not given onion peel powder, a significant increase in the average density of astrocytes was observed (p < 0.0001). Conclusions: The increased density of astrocytes in the hippocampus of obese animals can probably have a beneficial effect on brain changes in overweight individuals. The inclusion of onion in the diet of overweight/obese individuals may lead to increased hippocampal neuroplasticity, manifested by changes in the immunoexpression of LepRs. It can be speculated that the observed changes have a protective effect on the CNS structures during obesity, but this undoubtedly requires further research.